Nursing Care Analysis of the Effect of Dry Cupping Therapy to Reduce Blood Pressure in Hypertension Patients - Putra, I Made Cakra Yudiana; Heri, Mochamad; Putra, G. Nur Widya (Indonesian Journal of Global Health Research, 2024)
Hypertension is one of the most common non-communicable diseases suffered by society. Hypertension is known as the silent killer and the leading cause of death in the world because this disease can cause death without causing any symptoms. Hypertension or high blood pressure, where hypertension has several varied symptoms, such as headaches/pain in the nape of the neck, dizziness, dizziness, the many impacts of hypertension make it require appropriate treatment. Non-pharmacological therapy that can be used to reduce hypertension includes one of the alternative options for treating hypertension. What is currently recommended is cupping therapy. Cupping is considered faster for reducing high blood pressure, especially dry cupping. Dry cupping is a non-pharmacological therapy that is effective in lowering blood pressure in hypertension sufferers. The effect of cupping on blood pressure is to calm the sympathetic nervous system. This flexibility of the sympathetic nervous system stimulates the secretion of enzymes that work like the renin-angiotensin system so that blood pressure decreases. Objective: To explain complementary nursing care for the main problem of high blood pressure in hypertensive patients with the innovative intervention of dry cupping therapy. Results: The results of this study provided dry cupping therapy to reduce blood pressure in hypertensive sufferers using a descriptive research design in the form of a case study that identified a nursing care problem in hypertensive patients. From the nursing action of giving cupping therapy once at the specified time, it was found that the patient's blood pressure decreased significantly. It is recommended that hypertensive patients do dry cupping once a week as an alternative option to lower blood pressure. Cupping is considered faster in reducing high blood pressure and reducing pain in hypertensive sufferers due to high blood pressure